Impact of a sharing economy and green energy on achieving sustainable economic development: Evidence from a novel NARDL model - Chiu-Lan Chang; Ming Fang (Journal of Innovation & Knowledge (JIK), 2023)
Recently, the sharing economy has become a significant factor in sustainable economic development (SED), and green energy plays a role in this regard, a phenomenon which requires researchers' frequent emphasis. Thus, the present research investigates the impact of a sharing economy (sharing economy users and sharing economy values) and green energy (renewable energy production and consumption) on achieving SED in China. The article takes inflation and foreign direct investment (FDI) as the control variables. The research uses secondary data extracted from World Development Indicators (WDI) and Statista from 1991 to 2020. It applies the nonlinear autoregressive distributed lagged (NARDL) model to examine the linkages among the constructs. The results reveal that sharing economy users, sharing economy values, renewable energy production (REP), renewable energy consumption (REC), FDI, and inflation are positively linked with SED achievement in China. This article can help regulators develop regulations related to the achievement of SED using the sharing economy and green energy.
Keywords: 650; Green energy; Renewable energy production; Sharing economy users; Sharing economy values; Sustainable economic development